2019
DOI: 10.1002/ece3.5600
|View full text |Cite
|
Sign up to set email alerts
|

Functional response of wolves to human development across boreal North America

Abstract: Aim The influence of humans on large carnivores, including wolves, is a worldwide conservation concern. In addition, human‐caused changes in carnivore density and distribution might have impacts on prey and, indirectly, on vegetation. We therefore tested wolf responses to infrastructure related to natural resource development (i.e., human footprint). Location Our study provides one of the most extensive assessments of how predators like wolves select habitat in response to various degrees of footprint across b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 66 publications
(119 reference statements)
5
53
1
Order By: Relevance
“…Yet, Zeller et al ( 2019 ) found individual differences in resource choices in black bears even when accounting for behavioral state. Future studies might reveal that behaviorally explicit resource choices by coyotes are also individually variable, perhaps by a functional response to human presence or disturbance (as seen in wolves; Muhly et al 2019 ), spatial learning (Merkle et al 2019 ), or genotypic or phenotypic expressions (such as boldness; Wurth 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, Zeller et al ( 2019 ) found individual differences in resource choices in black bears even when accounting for behavioral state. Future studies might reveal that behaviorally explicit resource choices by coyotes are also individually variable, perhaps by a functional response to human presence or disturbance (as seen in wolves; Muhly et al 2019 ), spatial learning (Merkle et al 2019 ), or genotypic or phenotypic expressions (such as boldness; Wurth 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, while wolves (Canis lupus) generally avoid hunting in closed coniferous forests [12,16], they take advantage of linear features such as roads (from forestry and other source) and other corridors (e.g., seismic exploration cut-lines from oil and gas exploration) [17] to venture into forests which diminishes the effectiveness of caribou habitat-selection strategies to avoid predation [18]. The response of predators like wolves to using logging-impacted habitat across boreal caribou range is also non-linear, increasing with prevalence of cutblocks on the landscape [19]. Consequently, caribou generally experience higher mortality and especially lower recruitment in areas characterized by a relatively large proportion of anthropogenic disturbance [9,20].…”
Section: Introductionmentioning
confidence: 99%
“…Despite declining global populations and habitats, carnivores can be resilient and adapt to modified environments. Recent efforts to model future habitat and responses to development can provide managers with the tools to mitigate habitat loss or degradation and promote coexistence 116 119 . Conservation of carnivore populations globally will require clear and effective communication by scientists and the support of communities and governments.…”
Section: Discussionmentioning
confidence: 99%